Pengaruh Desain Produk,Kualitas Produk, Dan Harga Produk Terhadap Keputusan Pembelian Batik Khas Kota Mojokerto Pada Industri Batik “Bu Dar” - Arindah Triska Afandi; Imam Baidlowi; Agoes Hadi Poernomo (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
The Indonesian region has a variety of cultures and a variety of arts. One of the famous cultural heritage is batik. Batik is a cultural heritage from our ancestors since ancient times which was born as a work of art that has a philosophy about the meaning of life. Batik is an Indonesian heritage that really needs to be preserved because batik is a typical Indonesian textile that has motifs that have high artistic value. Batik that is traded has attractiveness through design, quality, price and other aspects that influence consumer purchasing decisions. This study aims to determine the effect of product design, product quality, and product prices on purchasing decisions for Mojokerto typical batik in the "Bu Dar" batik industry. This study uses a quantitative method with a sample of 100 respondents with the help of IBM SPSS. The results of this study indicate that partially the product design variable has a positive and significant effect on purchasing decisions with a t-count value of 2.281 > t-table 1.661 with a sig value of 0.025 <0.050 (5%), partially product quality variable has a positive and significant effect on purchasing decisions with a t-count value of 2.483 > t table 1.661 with a sig value of 0.015 <0.050 (5%), partially product price variable has a positive and significant effect on decisions purchases with a t value of 6.445 > t table of 1.661 with a sig value of 0.000 <0.050 (5%), while simultaneously the variables Product Design, Product Quality, and Product Price have a positive and significant effect on purchasing decisions for "Bu Dar" Batik with an F count of 54.167 > F table 2.699 with a sig value of 0.000.